Honor, Gaji, dan Tunjangan dalam Pendidikan Persepektif Hadis - Lisa Wahyuni Lubis; Selpi Cahyani; Welsya Nopi Olivia (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Journal this paper explores the concepts of honorarium, salary, and allowances in the field of educantion from the perspective of Prophentic tradition (hadith). The study is grounded in the undertanding that education plays a central role in shaping future generations, and teachers, as key contributors, deserve fair and proper compensation for their service. Despite their crucial role, many educators especially honorary teachers often face challenges due to insuffient financial recognition. This research examines various hadiths that emphasize the virtue of lawful work, the obligation to provide wages fairly and on time, and the importance of upholding justice and benevolence in human relationships. This study emplos qualitative library research by analyzing classical hadith compilation and scholarly interpretation. The findings highlight that fair compensation is not merely an economic issue but a moral and religious oblagation, reinforcing the need for enducational institutions to ensure teachers welfare in accordance with Islamic ethical principles.